1985
DOI: 10.1021/bi00335a022
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inhibitors of .beta.-glucosidase

Abstract: A variety of reversible inhibitors of sweet almond beta-glucosidase were examined. These included simple sugars and sugar derivatives, amines and phenols. With respect to the sugar inhibitors and, indeed, the various glycoside substrates, the enzyme has what can be considered a "relaxed specificity". No single substituent on glucose, for example, is essential for binding. Replacement of a hydroxyl group with an anionic substituent reduces the affinity while substitution with a cationic (amine) substituent enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(131 citation statements)
references
References 32 publications
(43 reference statements)
6
120
0
5
Order By: Relevance
“…No significant differences in this respect were observed between the two enzymes. The data described in this study confirm earlier studies of this enzyme from other organisms (Dale et al, 1985). CBL produces a characteristic competitive type of inhibition of cellobiose hydrolysis with a corresponding Ki of 27 f 6 p~.…”
Section: Cbl As a Substrate Of T Reesei P-glucosidasessupporting
confidence: 89%
“…No significant differences in this respect were observed between the two enzymes. The data described in this study confirm earlier studies of this enzyme from other organisms (Dale et al, 1985). CBL produces a characteristic competitive type of inhibition of cellobiose hydrolysis with a corresponding Ki of 27 f 6 p~.…”
Section: Cbl As a Substrate Of T Reesei P-glucosidasessupporting
confidence: 89%
“…In particular, ␦-gluconolactone, an inhibitor of lysozyme (K i ϭ 200 M), and ␦-gluconolactam, an inhibitor of sweet almond ␤-glucosidase B (K i ϭ 29 M), resemble the half-chair conformation but lack a positive charge (30,31). The cyclic amine inhibitors including 1-deoxynojirimycin (K i ϭ 18 M for sweet almond ␤-glucosidase), castanospermine, and australine rely on charge complementarity between the protonated nitrogen and negatively charged active-site carboxylates (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic amine inhibitors including 1-deoxynojirimycin (K i ϭ 18 M for sweet almond ␤-glucosidase), castanospermine, and australine rely on charge complementarity between the protonated nitrogen and negatively charged active-site carboxylates (20,21). However, evidence suggesting that the nonprotonated species may be the true inhibitory agents casts some uncertainty on the precise mechanism of inhibition (30). The cyclic amidines (32), which combine the half-chair conformation and positive charge, inhibit ␤-glucosidase with a K i of roughly 10 M. The short lifetimes of the latter at physiological pH preclude their use as haptens to elicit catalytic antibodies (ref.…”
Section: Resultsmentioning
confidence: 99%
“…7 A [19]. Dale et al [20] have examined the affinities of various sugar analogues for almond j3-glucosidase and have reported that the sugar analogues with the higher affinity for the enzyme have the hydroxyl groups at C2 and C3 diequatorial in their most stable conformation. It is interesting to note that removal of the hydroxyl group at C2 in glucose slightly reduces the affinity, suggesting a favorable interaction between the hydroxyl group at C2 and the enzyme.…”
Section: Discussionmentioning
confidence: 99%